PENERAPAN MODEL STAD UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, DAYA JUANG DAN PENGUASAAN KONSEP HIDUP MENGGEREJA PELAJARAN AGAMA KELAS V SEKOLAH XYZ: THE IMPLEMENTATION OF STAD MODEL TO ENHANCE CRITICAL THINKING SKILLS, RESILIENCE, AND MASTERY OF THE CONCEPT OF ECCLESIAL LIFE IN RELIGIOUS LESSON FOR FIFTH GRADE STUDENTS AT TARAKANITA ELEMENTARY SCHOOL - Seda, Fredirikus Seda; Winardi, Yonathan (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
Abstract The experience of the teaching and learning process after the Covid-19 pandemic shows a decrease in the resilience attitude of the students of XYZ school. Not only critical thinking skill as one of the skills in the 21st century expected by the school that needs to be developed by students, but the concept of church life is also quite difficult for grade V students to understand. Thus, the purpose of this research is to implement the STAD (Student Teams Achievement Divisions) learning model to enhance critical thinking skills, resilience, and mastery of the concept of church life in class V religious subjects of XYZ elementary school by conducting classroom action research (CAR). Three instruments were used: questionnaires, observations, and tests. The data analysis results showed that the implementation of the STAD model can enhance critical thinking skills, resilience and mastery of the concept of church life for grade V C students of XYZ school. Future researchers can use this study as a basis for research related to the measured variables while also considering the proportionality of the number of students and classroom size to implement the STAD model more effectively.